Evolutionarily Conserved Heterogeneous Nuclear Ribonucleoprotein (hnRNP) A/B Proteins Functionally Interact with Human and Drosophila TAR DNA-binding Protein 43 (TDP-43) - Romano, Maurizio (American Society for Biochemistry and Molecular Biology, 2014)
Human TDP-43 represents the main component of neuronal inclusions found in patients with neurodegenerative diseases, especially frontotemporal lobar degeneration and amyotrophic lateral sclerosis. In vitro and in vivo studies have shown that the TAR DNA-binding protein 43 (TDP-43) Drosophila ortholog (TBPH) can biochemically and functionally overlap the properties of the human factor. The recent direct implication of the human heterogeneous nuclear ribonucleoproteins (hnRNPs) A2B1 and A1, known TDP-43 partners, in the pathogenesis of multisystem proteinopathy and amyotrophic lateral sclerosis supports the hypothesis that the physical and functional interplay between TDP-43 and hnRNP A/B orthologs might play a crucial role in the pathogenesis of neurodegenerative diseases. To test this hypothesis and further validate the fly system as a useful model to study this type of diseases, we have now characterized human TDP-43 and Drosophila TBPH similarity in terms of protein-protein interaction pathways. In this work we show that TDP-43 and TBPH share the ability to associate in vitro with Hrp38/Hrb98DE/CG9983, the fruit fly ortholog of the human hnRNP A1/A2 factors. Interestingly, the protein regions of TDP-43 and Hrp38 responsible for reciprocal interactions are conserved through evolution. Functionally, experiments in HeLa cells demonstrate that TDP-43 is necessary for the inhibitory activity of Hrp38 on splicing. Finally, Drosophila in vivo studies show that Hrp38 deficiency produces locomotive defects and life span shortening in TDP-43 with and without animals. These results suggest that hnRNP protein levels can play a modulatory role on TDP-43 functions.